2021
DOI: 10.31729/jnma.6020
|View full text |Cite
|
Sign up to set email alerts
|

Pes Planus Foot among the First and Second Year Medical Students of a Medical College: A Descriptive Cross-sectional Study

Abstract: Introduction: Foot is a complex segmented structure formed by the articulation of 26 different bones which are held together by multiple ligaments, extrinsic tendons and the intrinsic muscles of the feet. The assessment of median longitudinal arch serves as an important reference in determining the degree of pes planus or pes cavus. This study aims to find the prevalence of pes planus among the undergraduate medical students of a medical college. Methods: A descriptive cross-sectional study was carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
1
Order By: Relevance
“…Similarly, the previous study in the medical students of Nobel Medical College, Nepal, showed normal arched foot followed by pes cavus and pes planus, respectively. 10 In contrast with CSI and SI classification, this study showed that a normal arched foot was the most prevalent, then pes planus, and pes cavus, respectively. Likewise, the previous study in medical students of Mahatma Gandhi Medical College and Research Institute, India, and in the physiotherapy students of Isra Institute of rehabilitation sciences, Pakistan, showed the most prevalent foot arch type was normal arched foot followed by pes planus and pes cavus, respectively.…”
Section: Discussioncontrasting
confidence: 69%
“…Similarly, the previous study in the medical students of Nobel Medical College, Nepal, showed normal arched foot followed by pes cavus and pes planus, respectively. 10 In contrast with CSI and SI classification, this study showed that a normal arched foot was the most prevalent, then pes planus, and pes cavus, respectively. Likewise, the previous study in medical students of Mahatma Gandhi Medical College and Research Institute, India, and in the physiotherapy students of Isra Institute of rehabilitation sciences, Pakistan, showed the most prevalent foot arch type was normal arched foot followed by pes planus and pes cavus, respectively.…”
Section: Discussioncontrasting
confidence: 69%